Pengaruh Efektivitas Pengendalian Internal, Profesionalisme Badan Pengawas Dan Moralitas Manajemen Terhadap Kecenderungan Kecurangan Akuntansi Pada Lembaga Perkreditan Desa (LPD) Se-Kecamatan Denpasar Selatan - Ni Made Ari Suryani; I Putu Deddy Samtika Putra (UNHI Press, 2023)
In order to limit the risk of fraud in village credit institutions, this document is structured in such a way that the elements that cause fraud, such as the effectiveness of internal control, the professionalism of the supervisory body, and the morality of management, may be determined afterwards. The research population consisted of 10 operational LPDs with 162 employees. The sample size is 89, with purposive sampling as the method of selection and regression analysis as the method of testing. The findings of this study show that internal control efficacy, supervisory body professionalism, and competent management can all help to lower the level of fraud in an institution. This study can be used as an example for firms that want to avoid high levels of accounting fraud in their own operations.